Treatment of a Unilateral Malposed Lower Molar by Mini-Plate Application - A Case Report - Cumhur Tuncer; Sancar Ataç; Emre Kaan; Burcu Baloş-Tuncer; Oktay Üner (Galenos Yayinevi, 2007)
Orthodontic correction of single tooth malpositions due to eruption problems, early loss of tooth and other reasons, is an important issue especially in patients with ideal occlusion without bonding the whole arch. In this case report treatment of a 9-year-old female patient with an Angle class I malocclusion having her right lower permanent first molar tilted mesially towards the space occurred by the extraction of right second deciduous molar tooth was presented. Correction of right upper lateral tooth which was located palatally is also included. A mini-plate which is used currently in recent years was used for direct anchorage to make unilateral lower molar distalization and uprighting in this case. After 7 months, enough distalization and uprighting was maintained. Afterwards the eruption of right lower second premolar was followed and the treatment was finished.